2019
DOI: 10.3171/2019.1.spine1814
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized controlled trial of tranexamic acid in minor lumbar spine surgery: no effect on operative time, intraoperative blood loss, or complications

Abstract: OBJECTIVEThe purpose of this study was to investigate the effect of tranexamic acid (TXA) compared to placebo in low-risk adult patients undergoing elective minor lumbar spine surgery—specifically with respect to operative time, estimated blood loss, and complications. Studies have shown that TXA reduces blood loss during major spine surgery. There have been no previous studies on the effect of TXA in minor lumbar spine surgery in which these variables have been evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Zhang et al [17] in 2019 conducted a meta-analysis of 11 studies, a total of 748 patients, and were able to show that intravenous TXA could effectively reduce IBL and perioperative blood transfusion during multilevel spine surgery, and could restore Hb level after surgery. Elmose et al [18] demonstrated that there was no statistically significant effect Total (95% CI) Heterogeneity: tau 2 = 0.04, chi 2 = 14.27, df = 8 (P = 0.08); I 2 = 44% Test for overall effect: Z = 3.15 (P = 0.002) Test for subgroup differences: chi 2 = 0.75, df = 1 (P = 0.39); I 2 = 0% - Heterogeneity: tau 2 = 0.00, chi 2 = 0.15, df = 2 (P = 0.93); I 2 = 0% Test for overall effect: Z = 3.99 (P < 0.0001)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [17] in 2019 conducted a meta-analysis of 11 studies, a total of 748 patients, and were able to show that intravenous TXA could effectively reduce IBL and perioperative blood transfusion during multilevel spine surgery, and could restore Hb level after surgery. Elmose et al [18] demonstrated that there was no statistically significant effect Total (95% CI) Heterogeneity: tau 2 = 0.04, chi 2 = 14.27, df = 8 (P = 0.08); I 2 = 44% Test for overall effect: Z = 3.15 (P = 0.002) Test for subgroup differences: chi 2 = 0.75, df = 1 (P = 0.39); I 2 = 0% - Heterogeneity: tau 2 = 0.00, chi 2 = 0.15, df = 2 (P = 0.93); I 2 = 0% Test for overall effect: Z = 3.99 (P < 0.0001)…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al 2018 Wu et al 2016 Zheng et al 2019 Subtotal (95% CI) Heterogeneity: tau 2 = 3.31, chi 2 = 22.60, df = 2 (P < 0.0001); I 2 = 91% Test for overall effect: Z = 0.27 (P = 0.79) Total (95% CI) Heterogeneity: tau 2 = 2.97, chi 2 = 66.85, df = 5 (P < 0.00001); I 2 = 93% Test for overall effect: Z = 0.56 (P = 0.58) Test for subgroup differences: chi 2 = 1.55, df = 1 (P = 0.21); I 2 = 35.3% - of intravenous TXA on intraoperative blood loss, operative time, or complications during minor lumbar spine surgery. However, intravenous TXA may have potentially adverse effects on patients, including DVT, PE, and myocardial infarction [18,19]. Intravenous TXA is usually avoided in patients with a previous history of myocardial infarction, DVT/ PE, stroke, and seizure disorders [20][21][22][23].…”
Section: Postoperative Aptt (Seconds)mentioning
confidence: 99%
“…For instance, previous studies had shown a reduction in blood loss when using TXA during major spine surgery. Therefore, Elmose et al 17 conducted a double-blind randomized controlled trial to investigate the impact of TXA in minor lumbar spine surgery. They found no statistically significant impact on operative time, intraoperative blood loss, or complications much like our findings 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Elmose et al 17 conducted a double-blind randomized controlled trial to investigate the impact of TXA in minor lumbar spine surgery. They found no statistically significant impact on operative time, intraoperative blood loss, or complications much like our findings 17 . In addition, our preexisting protocol of tumescent solution infiltration in breast reduction surgery may already achieve a significant level of reduction in blood loss and operative time, rendering the potential impact of TXA minimal at best.…”
Section: Discussionmentioning
confidence: 99%
“…Despite heterogeneity in dosing regimens for TXA, good evidence in support of TXA exists including metaanalyses of randomized control trials demonstrating efficacy in reducing blood transfusions and minimizing complications associated with major and complex multilevel spinal surgery. [36][37][38] The benefits versus risks of administration of TXA for minor lumbar surgery is disputable, 39 and published ERAS protocols typically reserve its use for complex cases. 2 Thus, the low use of TXA in our analysis is likely due to a majority of the cases being minor or a low number of levels fused ( ≤ 3 levels).…”
Section: Discussionmentioning
confidence: 99%